Role of Chromatin Architecture in Plant Stress Responses: An Update - Bhadouriya, Sneha Lata; Mehrotra, Sandhya; Basantani, Mahesh K.; Loake, Gary J.; Mehrotra, Rajesh (Frontiers in Plant Science, 2021)
Sessile plants possess an assembly of signaling pathways that perceive and transmit environmental signals, ultimately resulting in transcriptional reprogramming. Histone is a key feature of chromatin structure. Numerous histone-modifying proteins act under different environmental stress conditions to help modulate gene expression. DNA methylation and histone modification are crucial for genome reprogramming for tissue-specific gene expression and global gene silencing. Different classes of chromatin remodelers including SWI/SNF, ISWI, INO80, and CHD are reported to act upon chromatin in different organisms, under diverse stresses, to convert chromatin from a transcriptionally inactive to a transcriptionally active state. The architecture of chromatin at a given promoter is crucial for determining the transcriptional readout. Further, the connection between somatic memory and chromatin modifications may suggest a mechanistic basis for a stress memory. Studies have suggested that there is a functional connection between changes in nuclear organization and stress conditions. In this review, we discuss the role of chromatin architecture in different stress responses and the current evidence on somatic, intergenerational, and transgenerational stress memory.